Exploring the functional area approach in EU urban strategies (Transactions of the Association of European Schools of Planning, 2020)
A vast literature has investigated processes of spatial reconfiguration, contributing to the emergence of a ‘new urban question’ that not only reframes traditional urban issues but also challenges our understanding of what cities are today. Be that as it may, the ‘European city model’ still remains current, particularly with regards to the institutional role of cities as they are increasingly considered to be relevant policy actors. This urban paradox gives new emphasis to the urban regional scale and urgently calls for the two dimensions to be connected both in terms of territorial dynamics and policy formulation. This paper addresses the topic by focusing on the functional area approach promoted by the European Union regional policy discourse, and by discussing how it shapes and legitimates new spatial configurations, with implications for urban analysis and policy approaches. The paper is based on the analysis of a database which gathers nearly 1000 strategies for Sustainable Urban Development funded by the EU between 2014-2020, and features a significant number of functional areas. The analysis reveals that the functional area approach does not only apply to metropolitan areas, big cities, or Functional Urban Areas, but can also be used for different types of territories, beyond metropolitan areas. It also underscores the need for more extensive research on what spatialities and territorial arrangements emerge from this process.
Keywords: EU urban policy; sustainable urban development; FUAs; strategic planning